Alipogene tiparvovec: a long journey of risk-benefit ratio assessment of gene therapy products - R. N. Alyautdin; B. K. Romanov; A. P. Pereverzev; A. O. Chikalo; N. D. Bunyatyan; V. A. Merkulov; A. N. Mironov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
According to EMA, advanced therapy medicinal products include, inter alia, therapeutic systems containing nucleic acids used for replacement or repair of genetic defects. Alipogen tiparvovec, a medicine containing genetic material for treatment of hereditary deficiency of lipoprotein lipase, meets these criteria. The article summarizes pathophysiological principles of this medicine action in subjects with lipoprotein lipase deficiency. The article describes the results of preclinical research conducted in mice and cats. Clinical trials revealed its efficiency in patients with hereditary lipoprotein lipase deficiency, however the period during which the drug proved efficient was rather short. Nevertheless the data obtained from alipogen tiparvovec clinical trials were convincing enough for EMA to permit its application in clinical practice.